Modified Adomian Decomposition Method for Solving Fractional Singular Boundary Value Problems of Higher-Order Ordinary Differential Equations - Zainab Ali Abdu AL-Rabahi; Yahya Qaid Hasan (IJRDO -JOURNAL OF MATHEMATICS, 2020)
This paper is an attempt to solve fractional singular boundary value problems of higher-order ordinary differential equations by formulating a new modification of the Adomian decomposition method (MADM). The proposed method can be applied to both to linear and nonlinear problems. Therefore, it is tested with some examples and the obtained results were noticed to approximate the exact solutions. It can be concluded that this formulated modification of ADM is efficient and reliable to solve such kinds of problems.